Pediatric Dosing of Ganciclovir and Valganciclovir: How Model‐Based Simulations Can Prevent Underexposure and Potential Treatment Failure. (18th December 2018) - Jorga, Karin; Reigner, Bruno; Chavanne, Clarisse; Alvaro, Giuseppe; Frey, Nicolas
Abstract : Intravenous ganciclovir and oral valganciclovir are effective in the prevention and treatment of pediatric cytomegalovirus (CMV) infection but various dosing regimens are used in medical practice. Population pharmacokinetic (PopPK) model‐based simulations were used to propose a new ganciclovir pediatric dosing algorithm for regulatory review and to evaluate the approved valganciclovir pediatric dosing algorithm against published dosing recommendations derived from quantitative approaches. Oral valganciclovir (mg = 7 × body surface area (BSA) × creatinine clearance according to the Schwarz formula (CrCLS) daily) and i.v. ganciclovir (mg = 3 × BSA × CrCLS daily) are effective in reaching ganciclovir target exposure for the prevention of CMV (area under the concentration‐time curve (AUC)0–24 40–60 μg ∙ hour/mL) in most pediatric patients across the full pediatric age range. In contrast, ganciclovir and valganciclovir dosing based on body weight, as commonly used in medical practice, leads to underexposure, particularly in younger pediatric patients. This example shows that model‐based dosing algorithms built on clinical pharmacology and implemented using good modeling practice can prevent underexposure and reduce the risk of treatment failure in pediatric patients.